Sistema de mesa de ayuda (help desk) aplicando un modelo de desarrollo de software ágil para gestionar acciones en un ambiente distribuido - Jara Obregón, Julio Enrique (Machala : Universidad Técnica de Machala, 2023)
According to the policies established by the agencies in charge of guaranteeing the quality of Higher Education in Ecuador, there is a need to implement mechanisms to eliminate barriers to access, permanence and completion of higher education studies; components related to the analysis of students' academic performance. In this sense, a Decision Support System (DSS) was developed contemplating the activities described in the Hephaestus and Kimball methodologies; which uses as a set of data information from the student welfare department (student data), the Human Resources department (faculty data) and the academic system of the institution (student grades). The proposed DSS generates consolidated information through statistical graphs and, using Pearson's correlational coefficient, calculates a measure of linear dependence between two of the variables studied (grade point average, marital status, gender, household income, source of study resources, type of household and type of housing) in order to determine the type and degree of association of the factors that influence student academic performance. Subsequently, using usability evaluation criteria of business intelligence systems, a survey was applied as a data collection instrument to the personnel involved in decision making; with the results, the Chi-square statistic was determined with a significance level of 5%, thus concluding that the implementation of a DSS optimizes time and human resources in the generation of consolidated reports that support the analysis of the indicators that influence academic performance. In future work, we recommend the inclusion of data sets that could be generated by the institution's subsystems such as research projects, outreach projects and publications, which will significantly enrich the DSS and thus support the decision-making process.
Los modelos de desarrollo de software ágil se centran en el correcto flujo de conversación entre los clientes y el equipo de desarrollo, permitiendo que el proyecto se desarrolle de forma dinámica y participativa. Sin embargo, los modelos ágiles también tienen limitaciones en cuanto a la comprensión de problemas y la búsqueda de soluciones, principalmente debido a la aplicación de estos modelos con enfoques inadecuados. La comunidad investigadora ha prestado atención a los problemas relacionados con el desarrollo de software ágil, la presente investigación propone crear un modelo de desarrollo de software ágil híbrido que permita, la gestión del proceso de desarrollo de software respaldado por marcos de trabajo/metodologías/estándares/principios ágiles reconocidos, para ello, se analizaron 4 modelos: ASD, XP, Scrum y DevOps mediante criterios de inclusión y exclusión, combinando las potencialidades de cada uno por cada fase de desarrollo. El tipo de estudio realizado fue exploratorio y descriptivo pues se realizó un análisis detallado de las condiciones que demandan la necesidad de crear un nuevo modelo de desarrollo, se estableció usar un enfoque cuantitativo y cualitativo con la aplicación de los métodos teóricos inductivo – deductivo y analítico – sintético. El modelo propuesto fue validado por expertos a través de la ISO/CEI/IEEE 26515:2018 y el índice CSAT evidenciando la gestión eficiente de los procesos de desarrollo de información del proyecto de software, así como el índice de satisfacción del usuario-cliente. Finalmente, la aplicación del modelo propuesto permitió la entrega de módulos de software funcionales en el tiempo establecido, también ayudó al equipo a identificar las deficiencias
Keywords: DESARROLLO AGIL DE SOFTWARE; METODOLOGIA DE DESARROLLO AGIL; METODOS AGILES; METODOLOGIAS DE DESARROLLO DE SISTEMAS